Quantifying ventilatory control with 3% CO2 inhalation during exercise - Hashem, Suhaib M.; Yamashiro, Stanley M.; Kato, Takahide; Matsumoto, Takaaki; Marmarelis, Vasilis Z. (Frontiers in Physiology, 2025)
IntroductionCO2 mediated ventilation is mainly controlled by two homeostatic mechanisms. The central chemoreceptors are slower mechanisms that focus on blood pH sensing in the brain stem while the peripheral chemoreceptors are quicker to respond and reside in the carotid bodies. Quantification of these mechanisms in humans remain debated.ObjectiveTo quantify the impact that the central and peripheral chemoreceptors have on ventilation in response to changes in PETCO2 during exercise with normoxic breathing and 3% CO2 inhalation.MethodSix healthy males participated in a 5-stage bike protocol with and without 3% CO2 inhalation. We analyzed the time series data of their breath-by-breath PETCO2 and ventilation and generated a one input–one output model via the Laguerre expansion technique (LET) to construct the gain function and quantify the low (0.002–0.029 Hz) and high (0.03–0.15 Hz) frequency components using the weighted gain averages (WGA) as estimators of central and peripheral chemoreflex mechanisms respectively.Results3% CO2 inhalation caused a significant increase the high frequency WGAs at rest and in all levels of exercise except heavy exercise. The low frequency WGAs, however, only maintain significance during rest and the baseline session of exercise.ConclusionChanges in WGA can be used as quantitative estimates of central and peripheral chemoreflexes. 3% CO2 activates both reflexes and is more apparent in the higher frequency WGAs during exercise due to the oxygen dependent mechanisms effects of exercise.